ISOLATION OF AMNIOTIC FLUID MESENCHYMAL STEM CELLS (AF MSCs) OBTAINED FROM CAESAREAN SECTIONS - Bobby Indra Utama (Andalas Obstetrics And Gynecology Journal, 2019)
Amniotic fluid is a liquid that fills the amniotic cavity which has defense and nutritional functions in fetal development. Human aterm amniotic fluid can be an ideal alternative as a source of mesenchymal stem cells, originating from the neonate. Preclinical studies of second and third trimester amnion fluid cells confirmed the number of potential donors from this wasted material. In several studies, AF-MSCs express mesenchymal markers such as CD90, CD73 (SH3, SH), CD105 (SH2), CD29, CD166, CD49e, CD58 and CD44 (MHC class I). These cells also express HLA-ABC antigens, CD 34, CD 45 which are hematopoietic markers, and endothelial CD31 markers. There is no expression of CD10, CD11b, CD14, CD34, CD117, EMA and HLA-DR, DP, DQ antigens. Most of AF-MSCs have pluripotent properties which are characterized by the discovery of octamer binding protein 3/4 (Oct-3/4), transcription factors Nanog (Nanog), and stage-specific embryonic antigen 4 (SSEA-4) on RT-PCR examination. From this study, 8 million cells was isolated. These cells will be used for research on pelvic organ prolapse therapy by using AF-MSCs. AF-MSCs isolation totally takes 6 weeks. From 1 flask, 2 million of stem cells was obtained. Keywords: amniotic fluid, AF-MSCs